Chlorambucil-iron oxide nanoparticles as a drug delivery system for leukemia cancer cells - Al-Ali, Samer Hasan Hussein; Hussein, Mohd Zobir; Bullo, Saifullah; Arulselvan, Palanisamy (Taylor and Francis, 2021)
Introduction: Traditional cancer therapies may have incomplete eradication of cancer or destroy the normal cells. Nanotechnology solves the demerit by a guide in surgical resection of tumors, targeted chemotherapies, selective to cancerous cells, etc. This new technology can reduce the risk to the patient and automatically increased the probability of survival. Toward this goal, novel iron oxide nanoparticles (IONPs) coupled with leukemia anti-cancer drug were prepared and assessed. Methods: The IONPs were prepared by the co-precipitation method using Fe+3/Fe+2ratio of 2:1. These IONPs were used as a carrier for chlorambucil (Chloramb), where the IONPs serve as the cores and chitosan (CS) as a polymeric shell to form Chloramb-CS-IONPs. The products were characterized using transmission electron microscopy (TEM), powder X-ray diffraction (PXRD), scanning electron microscopy (SEM) analysis, Fourier transform infrared spectroscopy (FTIR), vibrating sample magnetometry (VSM) analyses, and thermal gravimetric analysis (TGA). Results: The as-prepared IONPs were found to be magnetite (Fe3O4) and were coated by the CS polymer/Chloramb drug for the formation of the Chloramb-CS-IONPs. The average size for CS-IONPs and Chloramb-CS-IONPs nanocomposite was found to be 15 nm, with a drug loading of 19% for the letter. The release of the drug from the nanocomposite was found to be of a controlled-release manner with around 89.9% of the drug was released within about 5000 min and governed by the pseudo-second order. The in vitro cytotoxicity studies of CS-IONPs and Chloramb-CS-IONPs nanocomposite were tested on the normal fibroblast cell lines (3T3) and leukemia cancer cell lines (WEHI). Chloramb in Chloramb-CS-IONPs nanocomposite was found to be more efficient compared to its free form. Conclusion: This work shows that Chloramb-CS-IONPs nanocomposite is a promising candidate for magnetically targeted drug delivery for leukemia anti-cancer agents.